Celiac disease and non-celiac gluten sensitivity - Lebwohl, Benjamin (BMJ, 2015)
Celiac disease is a multisystem immune based disorder that is triggered by the ingestion of gluten in genetically susceptible individuals. The prevalence of celiac disease has risen in recent decades and is currently about 1% in most Western populations. The reason for this rise is unknown, although environmental factors related to the hygiene hypothesis are suspected. The pathophysiology of celiac disease involves both the innate and adaptive immune response to dietary gluten. Clinical features are diverse and include gastrointestinal symptoms, metabolic bone disease, infertility, and many other manifestations. Although a gluten-free diet is effective in most patients, this diet can be burdensome and can limit quality of life; consequently, non-dietary therapies are at various stages of development. This review also covers non-celiac gluten sensitivity. The pathophysiology of this clinical phenotype is poorly understood, but it is a cause of increasing interest in gluten-free diets in the general population.